Effects of crop species on indigenous microflora and of silage additives on the microbial succession during the ensiling process - Lin, C.; Hart, R.A.; Bolsen, K.K.; Dickerson, J.T.; Brent, B.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study considered the effects of crop species (alfalfa vs. corn) and silage additives on six categories of indigenous microorganisms (those naturally occurring on the crop) important to silage fermentation, and on the microbial succession during the ensiling process. The numbers of streptococci, Enterobacteriaceae, yeasts and molds, lactate-using yeasts, and carbohydrate- fermenting clostridial spores were higher on corn than on alfalfa. The lactic acid bacteria (LAB) comprised less than 2% of the total microbial populations on both crops. Alfalfa treated with Biomate® inoculant and the combination of dextrose and Biomate showed higher LAB counts than the control and dextrose treatments at 1 day post-ensiling. Adding dextrose accelerated multiplication of LAB in the ensiled alfalfa. Adding 1174® inoculant to corn silages did not affect the microbial succession during the ensiling process. Development of Enterobacteriaceae, yeasts and molds, lactate-using yeasts, and clostridia on either crop during ensiling was not influenced by the additives.
Keywords: Beef; Epiphytic microflora; Alfalfa; Corn; Additive; Silage